(untitled) (Research, Society and Development, 2024)
Coffee is the second most consumed beverage in the world, after water, and the second commodity in terms of turnover. Brazil is the largest producer of coffee, responsible for 1/3 of global production, and the largest exporter of unprocessed coffee with a yearly turnover of 800 million dollars. This income would increase if coffee consumption increased in Brazil, which requires sensitizing Brazilian consumers with scientific arguments on the benefits of coffee, scientifically rebutting the purported harms of its consumption. Arguing that coffee should be considered a nutraceutical would be a cornerstone of this sensitization. This article proposes to contribute, based on scientific evidence, to the creation, in Brazil, of a Coffee and Health Research Institute. To this end, a bibliographical review was carried out. We observed that, despite the economic importance of the coffee agribusiness, there is no Coffee and Health Research Institute in the world. Brazil is ideally positioned to implement such a pioneering Institute since we have numerous research groups internationally recognized for their studies on the impact of coffee on human health. This Institute would contribute to an increase in coffee consumption in Brazil, contradicting, with scientific evidence, the erroneous generalization that coffee is a "stimulant," with the potential for dependence and causing long-term damage, which would be a major economic contribution to the coffee industry in Brazil. A Federal Institution would have the economic and organizational scope to lead this Institute capable of steadily and sustainably increasing the income associated with coffee agribusiness.